2011
DOI: 10.1063/1.3609072
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation pinning effects induced by nano-precipitates during warm laser shock peening: Dislocation dynamic simulation and experiments

Abstract: Warm laser shock peening (WLSP) is a new high strain rate surface strengthening process that has been demonstrated to significantly improve the fatigue performance of metallic components. This improvement is mainly due to the interaction of dislocations with highly dense nanoscale precipitates, which are generated by dynamic precipitation during the WLSP process. In this paper, the dislocation pinning effects induced by the nanoscale precipitates during WLSP are systematically studied. Aluminum alloy 6061 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…For example, in 2015, Liao et al [14] reviewed the processing techniques of warm laser shock peening (WLSP) and thermal engineered-laser shock peening (TE-LSP) systematically and explained the fundamental process mechanisms clearly. According to the review, a dislocation pinning effect based on the dynamic strain aging (DSA) and dynamic precipitation (DP) is the main reason for improvement of residual stress and microstructure stability of WLSP [14,15]. Chen et al [16] in Jiangsu University studied the effects of warm laser peening (WLP) on thermal stability of the A356 alloy and found that WLP can effectively improve the thermal stability of residual stress compared with LP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2015, Liao et al [14] reviewed the processing techniques of warm laser shock peening (WLSP) and thermal engineered-laser shock peening (TE-LSP) systematically and explained the fundamental process mechanisms clearly. According to the review, a dislocation pinning effect based on the dynamic strain aging (DSA) and dynamic precipitation (DP) is the main reason for improvement of residual stress and microstructure stability of WLSP [14,15]. Chen et al [16] in Jiangsu University studied the effects of warm laser peening (WLP) on thermal stability of the A356 alloy and found that WLP can effectively improve the thermal stability of residual stress compared with LP.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in the radiation intensity and, hence, in the pressure and strain rate, the dislocation structure formed in the shock wave develops in the fol lowing sequence: uniform dislocation density distri bution-cellular dislocation structure-uniform dislo cation density distribution with stacking faults, and, finally, at pressures above 60 GPa, the formation of a strain induced structure consisting of microtwins [1][2][3][4]. In polycrystals, the character of the dislocation structure in a shock wave is determined by the grain size [5][6][7], whereas in alloys, the dislocation structure depends on the presence of precipitates in the material [7,8] and on the stacking fault energy [9]. As the pres sure increases above 1-10 GPa, the generation of geo metrically necessary dislocations at the shock wave front becomes a significant factor [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the real physical experiment, the char acter of dislocation structures formed in a shock wave has also been investigated using methods of molecular dynamics [10,11] and discrete dislocation dynamics [8,12] simulation. Owing to the visibility of computer simulation, these methods supplement experimental results and allow one to observe the formation of a dis location structure or its individual elements at differ ent scale levels.…”
Section: Introductionmentioning
confidence: 99%
“…The laser shock induced by pulse laser ablation under a confinement has been widely investigated because of its great potential for industrial applications, such as LSP [1][2][3][4][5][6], laser dynamic forming [7,8], and laser-assisted micromachining [9,10]. The capability, efficiency, and application range of these laser-based techniques are strongly governed by the intensity of laser shock.…”
mentioning
confidence: 99%